2001
DOI: 10.1007/bf03166848
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization zoning in Yindongzi-Daxigou barite-siderite, silver-polymetallic deposits in the Qinling orogen, China

Abstract: The Yindongzi-Daxigou strata-bound barite-siderite, silver-polymetallic deposits discovered in the Qinling orogen are hosted within flysch facies in a deep-water fault-controlled basin on the passive northern margin of the Qinling microplate . The orebodies occur in a series of hydrothermal depositional rocks. Mineralization zoning is characterized by Fe-Bam-Ba-Cu^-Pb-Ag-^Cu-Ag->Pb-'Au. This is obviously a gradational transition mineralization from ventproximal mineralization to more distal mineralization . In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The area with the content no more than 30 mg/kg accounted for 84.1% of the total area. In addition, the content of Cu is the highest; Pb is the second highest in the study area, which is consistent with the geochemical investigation mapping data [21]. Meanwhile, by comparing the two elements estimated in this study with the maximum and arithmetic mean values of the reference values of soil elements in Shaanxi Province, it is found that the content of the two elements in some parts of the study area exceed the average reference values of soil elements in Shaanxi Province, which indicates that the soil in some areas has been polluted by these two heavy metals since 1990.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The area with the content no more than 30 mg/kg accounted for 84.1% of the total area. In addition, the content of Cu is the highest; Pb is the second highest in the study area, which is consistent with the geochemical investigation mapping data [21]. Meanwhile, by comparing the two elements estimated in this study with the maximum and arithmetic mean values of the reference values of soil elements in Shaanxi Province, it is found that the content of the two elements in some parts of the study area exceed the average reference values of soil elements in Shaanxi Province, which indicates that the soil in some areas has been polluted by these two heavy metals since 1990.…”
Section: Resultssupporting
confidence: 89%
“…It is the largest siderite operation in Shaanxi, accounting for 47.6% of the total iron ore reserves. In 1982, the Northwest Metallurgical Geological Exploration Company found that the Daxigou-Yindongzi deposit is rich in copper, lead, zinc, silver, etc., in and around the mining area [21]. Mining in the area officially began in 1988, and open-pit mining has mainly been used since 2007.…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The mine is one of the largest siderite mines in China, accounting for 47.6% of the total iron ore reserves in Shaanxi Province. In 1982, it was discovered that the Daxigou-Yindongzi deposit was rich in Cu, Pb, Zn, Ag, and other minerals [21]. The mining activity officially began through open-pit mining in 1988.…”
Section: Overview Of the Study Areamentioning
confidence: 99%